2020
DOI: 10.1038/s41598-020-78423-x
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual blood-derived stromal cells modulate functional properties of mouse and human macrophages

Abstract: Menstrual blood-derived stromal cells (MenSCs) are emerging as a strong candidate for cell-based therapies due to their immunomodulatory properties. However, their direct impact on innate immune populations remains elusive. Since macrophages play a key role in the onset and development of inflammation, understanding MenSCs implication in the functional properties of these cells is required to refine their clinical effects during the treatment of inflammatory disorders. In this study, we assessed the effects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Studies using human specimens were conducted as indicated in a protocol approved by the Institutional Review Board at Baylor College of Medicine, H-51900. Human EnSCs were collected from healthy volunteers’ menstrual effluent as previously reported ( Warren et al, 2018 ; Nayyar et al, 2020 ; Martínez-Aguilar et al, 2020 ) (N = 3). In brief, samples were collected by participants in a DIVA cup during the 4–8 hr on the first night of menses and stored in DMEM/F12 with 10% FBS, antibiotic/antimycotic and 100 µg/ml Primocin in a cold-insulated pack until processing in the laboratory on the day of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using human specimens were conducted as indicated in a protocol approved by the Institutional Review Board at Baylor College of Medicine, H-51900. Human EnSCs were collected from healthy volunteers’ menstrual effluent as previously reported ( Warren et al, 2018 ; Nayyar et al, 2020 ; Martínez-Aguilar et al, 2020 ) (N = 3). In brief, samples were collected by participants in a DIVA cup during the 4–8 hr on the first night of menses and stored in DMEM/F12 with 10% FBS, antibiotic/antimycotic and 100 µg/ml Primocin in a cold-insulated pack until processing in the laboratory on the day of collection.…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 25, 2023. ; https://doi.org/10.1101/2023.09.25.559321 doi: bioRxiv preprint Studies using human specimens were conducted as indicated in a protocol approved by the Institutional Review Board at Baylor College of Medicine, H-51900. Human endometrial stromal cells were collected from healthy volunteers' menstrual effluent as previously reported [27][28][29] . (N=3) In brief, samples were collected by participants in a DIVA cup during the 4-8 hours on the first night of menses and stored in DMEM/F12 with 10% FBS, antibiotic/antimycotic and 100µg/ml Primocin in a cold insulated pack until processing in the laboratory on the day of collection.…”
Section: Primary Endometrial Stromal Cells Isolation/rnai/decidualiza...mentioning
confidence: 99%
“…MenSCs could suppress the apoptosis of MLE-12 cells via downregulating the expression of cytokines, such as GITR, GM-CSF, RANTES, MIP-1γ, eotaxin, MCP-5 and CCL1, which were involved with inflammatory reaction ( 31 ). In addition, in vitro studies demonstrated that MenSCs had a negative effect on macrophage bactericidal properties and the production of reactive oxygen intermediates, indicating that MenSCs effect the macrophage numbers, which provides a theoretical basis for clinical treatment in future ( 32 ). Moreover, MenSCs can have a negative effect on PI3K/Akt/mTOR/IKK signaling mediated by TLR4, leading to a decreasing of inflammatory cytokine, as p-NF-κBp65 could not be translocated into the nucleus ( 33 ).…”
Section: The Immunomodulatory and Anti-inflammatory Function Of Menscsmentioning
confidence: 99%